(untitled) (Canadian Medical Education Journal, 2026)
Implication Statement The Choosing Wisely Resource Stewardship Certificate demonstrates that students can meaningfully develop practical resource stewardship and evidence-informed decision-making skills through a virtual, interprofessional and case-based curriculum. We found that combining student-led discussions with guidance from diverse healthcare professionals helped learners connect resource stewardship theory to real-world clinical decisions and strengthen patient-centred care practices. The program’s virtual format allows institutions to implement flexible, effective content on resource stewardship to learners, addressing a key curriculum gap. Expanding the Choosing Wisely Resource Stewardship Certificate to include recorded sessions or asynchronous modules will further expand its impact.